Participation and Creative Autonomy:: The Changing Role of Artists - Berg, Ine Therese (Teatervitenskapelige studier, 2023)
In this article I analyze the implications of different forms of participation on the role of artists and their creative autonomy. Through a conceptual clarification around core ideas that are commonly associated with the pairing of participation and art, I discuss recent development in artistic practices. The concepts artistic autonomy and creativity have been central to the development of the professional role and identity that artists in the performing arts field have today. With this as a backdrop, I map out the conceptual differences between creative participation, aesthetic participation, democratic participation and civic participation, and how they impact artists. The article mainly draws on recent theory in performance studies and applied theatre, as well as sociological perspectives. Finally, I discuss how contemporary artists often combine different roles, even within a single work.